Renewal of the Scope of Medical Sciences - Yu-Jia Chang (Medical Sciences, 2015)
From time to time, it is useful to reassess a journal’s purpose, and position it in a way that it can make a significant and unique contribution to the scientific literature. I have recently completed the task of adjusting the scope of Medical Sciences (ISSN 2076-3271; http://www.mdpi.com/journal/medsci), and I believe it is now in an even better position to publish significant work that will be of use and interest to scholars and clinicians within the medical science field.[...]